2019
DOI: 10.1534/g3.118.200963
|View full text |Cite
|
Sign up to set email alerts
|

Generation of H11-albumin-rtTA Transgenic Mice: A Tool for Inducible Gene Expression in the Liver

Abstract: The modification of the mouse genome by site-specific gene insertion of transgenes and other genetic elements allows the study of gene function in different developmental stages and in the pathogenesis of diseases. Here, we generated a “genomic safe harbor” Hipp11 ( H11 ) locus-specific knock-in transgenic mouse line in which the albumin promoter is used to drive the expression of the reverse tetracycline transactivator (rtTA) in the liver. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In Malhotra's experiment, it was found that siRNA gene therapy with an albumin carrier, inhibit the expression of the genes involved to treat cancer [21]. In Li's experiment, the new H11-albumin-rTTA transgenic mice were found to be a powerful and effective tool for manipulating gene expression in the liver in both spatial and temporal conditions [22]. Lorraine's study evaluated the potential value of albuminuria as a "biomarker" for acute kidney injury (AKI) and examined whether AKI induces expression of normally silenced albumin genes in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…In Malhotra's experiment, it was found that siRNA gene therapy with an albumin carrier, inhibit the expression of the genes involved to treat cancer [21]. In Li's experiment, the new H11-albumin-rTTA transgenic mice were found to be a powerful and effective tool for manipulating gene expression in the liver in both spatial and temporal conditions [22]. Lorraine's study evaluated the potential value of albuminuria as a "biomarker" for acute kidney injury (AKI) and examined whether AKI induces expression of normally silenced albumin genes in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…It is situated between the Eif4enif1 gene and the Drg1 gene on chromosome 11, with no endogenous genes identified within this region. Several transgenic models inserted at this locus have confirmed its safety as a harbor [12][13][14].…”
Section: Introductionmentioning
confidence: 90%
“…Standard Hematoxylin and Eosin (H&E) staining was performed on paraffin sections as described previously [ 47 ]. Testes and cauda epididymides were freshly fixed in Davidson’s fixative solution (Formaldehyde: Ethanol: Glacial acetic acid: H 2 O = 6: 3: 1: 10) overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%